(untitled) (Marketing Journal, 2025)
This study explores the role of artificial intelligence in distributing household chemical products in the B2B market. It analyzes key functions such as demand forecasting, inventory optimization, recommendation systems, and supplier selection. Based on vi sual data and scholarly sources, the findings show that AI technologies help stabilize product flow, reduce costs, and offer solutions aligned with customer needs. The results confirm that integrating AI into B2B distribution models enhances precision, fle xibility, and economic efficiency. 366